Critical Reviews of IPAS Learning in Primary Education in Indonesia's Independent Curriculum - Faizal, Jefri; Ichsan, Ahmad Shofiyuddin (MASALIQ, 2025)
Learning Natural and Social Sciences (IPAS/Ilmu Pengetahuan Alam dan Sosial) in basic education has its benefits because it combines two sciences at once, namely science and social sciences. In reality, many dynamics are found in the learning process at school. For this reason, this study critically reveals the learning of IPAS in basic education in the Merdeka Curriculum. Researchers use qualitative research by using content analysis as the analysis technique. The results showed that IPAS learning has two essential elements, namely understanding IPAS theoretically and process skills in practice. IPAS learning must also implement three phases, from grade 1 to grade 6. Although it has many benefits, the reality is that there are challenges in the learning process, including teachers still depending on textual with the lecture method and very rapid curriculum changes that confuse teacher performance in teaching. The classroom environment is not entirely conducive. For this reason, stakeholders need to provide appropriate solutions, one of which is by giving many comprehensive teacher competency improvement programs.